O Uso da técnica de encapsulamento como alternativa para o emprego de solo contaminado por derivados de petróleo em camadas de base e sub-base de pavimentos - Cavalcante, Francisco das Chagas Isael Teixeira (2013)
The petrochemical industry or petroleum deserves special attention because, in practically all stages (drilling, refining, storage and distribution), residues that harm the environment and is a challenge to those responsible for their management are generated. Among the various wastes generated by the oil industry, are the Soils Contaminated by Petroleum Products (SCPD). In Ceará state, the generation of this type of waste is coming from a refinery that is located in Fortaleza city. During maintenance performed on the steps of refining and storage of petroleum, can occur contact derivatives with soil, contaminating it, thus generating SCPD which finishes stored in drums, requiring alternative for correct final disposal. Given the above, was decided to study the incorporation of SCDP in the granular layers of the floor so that it ensures no damage to the environment. A new methodology was developed allowing the assessment of the technical feasibility of using SCDP (natural or stabilized) in Road Paving, using the encapsulation technique with cement. In the experimental program developed, the characterization tests, compaction, California Bearing Ratio (CBR), Simple Compression Strength (RCS), Diametrical Compression (RTCD), Resilience Modulus (MR), durability were executed, thus as the achievement of the environmental tests of leaching and solubilization. Observed after conducting of the experimental program, there are technical possibility for the incorporation of SCDP in granular pavement layers. The results shown an incorporation of residue to the natural ground, in other words, a particle size stabilization already has considerable gains, since it increases the index support. By adding cement, significant gains were obtained from CBR, MR, RCS and RT, and a condition of reasonable durability. However, environmentally, in an initial assessment, the feasibility of using the SCDP on pavements was not possible, because the mix without cement and mixing with cement evaluated, obtained concentrations of the parameters analyzed in the assay solubilization above permitted. However, it is important to note that the current method of assessing contaminant parameters does not take into consideration conditions that might be encountered in the field, thus there is a need to design of a model to evaluate the mechanical and environmental properties for waste that may be incorporated in the pavement construction process. Thus, the encapsulation technique contaminants cannot be ignored as an alternative to incorporating SCDP granular layers of paving